Peningkatan karakter anak melalui program camping sebagai pembelajaran berbasis alam dalam di MJP Bandung - Prasanti, Ditha; Nabilla, Bening Putri; Rahmadini, Annisa Tri (Penamas: Journal of Community Service, 2025)
This article is the result of a Community Service (PKM) activity conducted with sixth-grade students at Madrasah Ibtidaiyah, focusing on the implementation of nature-based learning. The PKM activity aimed to enhance character development, creativity, social awareness, and environmental consciousness, all packaged into a camping programme at Manglayang Jungle Park (MJP) in Bandung. The PKM methods employed included tutorial-based instruction and simulation activities, such as teamwork in setting up tents, nature exploration, campfires, and bonding exercises, to foster camaraderie among peers. The PKM participants consisted of 26 students, a mix of boys and girls. The outcomes of the PKM activities are as follows: PKM participants demonstrated high enthusiasm for the concept of nature-based learning. This condition was reflected in their active participation and enthusiasm throughout the PKM programme from start to finish; PKM participants developed teamwork and social awareness through competitive activities, enhanced environmental awareness by maintaining cleanliness around the camping site, and improved their creativity through the “Crafting Nature Challenge”. Additionally, PKM participants developed communication skills with their peers through peer appreciation activities during the camping program.